ActionScript cookbook - Lott, Joey (O'Reilly, 2003)
When you need to get the job done fast, you'll reach for this practical, nuts-n-bolts toolkit. Rather than focusing on ActionScript in the abstract, this Cookbook puts theory into practice with ready-made answers to common ActionScript problems. Flash MX developers can solve issues quickly, while learning practical techniques for resolving similar dilemmas in the future. ActionScript has blossomed into a large and important language whose sheer volume of capabilities can be daunting. The ActionScript Cookbook breaks it all down into tasks that are relevant, practical, and insightful. Appealing to the budding coder as well as the experienced ActionScript jockeys, this book offers new perspectives and approaches to ActionScript development that will empower all developers. This O'Reilly Cookbook complements ActionScript for Flash MX: The Definitive Guide, 2nd Edition by providing quick solutions to common ActionScript problems. This book trades on our respected "Cookbook" approach, which provides a worked-out script for every problem addressed. You can use these "recipes" to solve an immediate problem, and then explore the issue further in The Definitive Guide when time permits. The ActionScript Cookbook contains over 300 recipes on a myriad of topics. Here's a sampling of what you'll find: Drawing shapes at runtime Controlling movie clips programmatically Accepting user input and manipulating text strings Accessing audio and video via Flash Communications Server Working with Flash Remoting to connect to back end databases Using record sets with data grids And, much, much more in over 20 recipe-laden chapters ... Building a Flash Paint Application Creating a Video/Chat Message Server Application Creating an MP3 Jukebox Creating a personalizable MyPage Application This Cookbook's logical progression from short recipes for small problems to longer, more complex scripts for thornier riddles allows developers to link modular ActionScript pieces together to create rock-solid solutions for Flash applications. If you prefer to see larger applications instead of atomic recipes, this Cookbook has a kicker -- seven full chapters of sample applications including: The ActionScript Cookbook is for people who say, "I understand everything in theory, but I don't know where to start in practice." This book is all about practice